Transcriptional and Epigenetic Regulation of Autophagy in Plants - Yang, Chao; Luo, Ming; Zhuang, Xiaohong; Li, Faqiang; Gao, Caiji (Trends in genetics, 2020)
Autophagy, a highly conserved quality control mechanism, is essential for maintaining cellular homeostasis and healthy growth of plants. Compared with extensive research in the cytoplasmic control of autophagy, studies regarding the nuclear events involved in the regulation of plant autophagy are just beginning to emerge. Accumulating evidence reveals a coordinated expression of plant autophagy genes in response to diverse developmental states and growth conditions. Here, we summarize recent progress in the identification of tightly controlled transcription factors and histone marks associated with the autophagic process in plants, and propose several modules, consisting of transcription regulators and epigenetic modifiers, as important nuclear players that could contribute to both short-term and long-term controls of plant autophagy at the transcriptional and post-transcriptional levels. Coordinated transcriptional upregulation of ATG genes emerges as a general mechanism of autophagy activation in plants.Recent studies unveil several key transcription factors involved in the transcriptional control of plant autophagy.HDA9 functions as an important epigenetic modifier to modulate plant autophagy in response to developmental or stress cues.Genome-wide studies illustrate the enrichment of specific epigenetic marks or nucleobase modifications on ATG loci in plants.